Schrier's diseases of the kidney. - Coffman, Thomas M.; Schrier, Robert W. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"The recent advances in many aspects of kidney diseases have mandated a new edition of Schrier's Diseases of the Kidney. As in previous editions, a group of international experts was assembled to present this information in a comprehensive, authoritative, concise, and readily accessible fashion. The chapters have been extensively revised and updated"--Provided by publisher.